Innovative trends in the teaching of English - Kryvonos, Iryna; Кривонос, Ірина Анатоліївна; Кривонос, Ирина Анатольевна (Мелітополь: Видавництво МДПУ, 2018)
EN: At the present stage, our country is opening up opportunities for integrating its culture, economy, politics and technology into the world space. Therefore, the value of a foreign language is very large, since it is a means of communication between peoples are an important instrument for integrating our homeland to world civilization; it is a means of discovery and knowledge of the world of Ukraine. All this leads to an increase in the requirements for knowledge of a foreign language acquired at school, to their use in the learning process and to the achievement of a standard level of knowledge that is adequate in the world.
Keywords: innovative methods of the educational; self-improvement of the educational